The Democratic Legacy of the International Criminal Court - Mayerfeld, Jamie (Tufts Archival Research Center, 2005)
Volume 28, Issue 2. Summer Jamie Mayerfeld argues that the ICC is an ingenious means of bolstering democracy and encouraging its spread, and, therefore, deserves support from those who believe in democratization as the key to protecting fundamental human rights.